Hubungan Tingkat Alexithymia dengan Kecanduan Media Sosial pada Remaja di SMA Negeri 1 Tuntang: The Relationship Between Alexithymia Levels and Social Media Addiction in Adolescents at SMA Negeri 1 Tuntang - Reike kumalasari; Mona Saparwati (Journal of Holistics and Health Sciences, 2026)
The development of digital technology has encouraged increased use of social media among adolescents, which has the potential to cause addiction because adolescents are still in the stage of emotional and social development. One psychological factor that is thought to play a role is alexithymia, which is the inability of individuals to recognize and express emotions. Adolescents with alexithymia tend to use social media as a means of emotional escape, thereby increasing the risk of addictive behavior. This study aims to determine the relationship between the level of alexithymia and social media addiction among adolescents in SMA Negeri 1 Tuntang. The study used a correlational quantitative design with a population of 336 tenth-grade students and a sample of 77 students determined using quota sampling techniques. The instruments used were the Toronto Alexithymia Scale (TAS-20) and the Bergen Social Media Addiction Scale (BSMAS). Data analysis was performed using the Chi-Square test. The results showed that most respondents were in the high alexithymia category (53.2%), while the level of social media addiction was mostly in the moderate category (35.1%). The Chi-Square test showed a significant relationship between the level of alexithymia and social media addiction). The conclusion of this study is that alexithymia is significantly related to social media addiction. Suggestions for future researchers include expanding the scope of research variables by examining other psychological aspects that play a role in addiction.   ABSTRAK Perkembangan teknologi digital mendorong peningkatan penggunaan media sosial pada remaja, yang berpotensi menimbulkan kecanduan karena remaja masih berada pada tahap perkembangan emosi dan sosial. Salah satu faktor psikologis yang diduga berperan adalah alexithymia, yaitu ketidakmampuan individu dalam mengenali dan mengekspresikan emosi. Remaja dengan alexithymia cenderung menggunakan media sosial sebagai sarana pelarian emosional sehingga meningkatkan risiko perilaku adiktif. Penelitian ini bertujuan untuk mengetahui hubungan tingkat alexithymia dengan kecanduan media sosial pada remaja di SMA Negeri 1 Tuntang. Penelitian menggunakan desain kuantitatif korelasional dengan populasi 336 siswa kelas X dan sampel sebanyak 77 siswa yang ditentukan menggunakan teknik quota sampling. Instrumen yang digunakan adalah Toronto Alexithymia Scale (TAS-20) dan Bergen Social Media Addiction Scale (BSMAS). Analisis data dilakukan menggunakan uji Chi-Square. Hasil penelitian menunjukkan sebagian besar responden berada pada kategori alexithymia tinggi (53,2%), sedangkan tingkat kecanduan media sosial paling banyak berada pada kategori sedang (35,1%). Uji Chi-Square menunjukkan terdapat hubungan yang signifikan antara tingkat alexithymia dengan kecanduan media sosial. Simpulan penelitian ini adalah alexithymia berhubungan signifikan dengan kecanduan media sosial. Saran bagi peneliti selanjutnya dapat memperluas cakupan variabel penelitian dengan mengkaji aspek psikologis lain yang berperan dalam kecanduan media sosial.